REGRESSION MODELS COMPUTED TOMOGRAPHY SIZES OF LUMBAR SPINE ON THE MEDIAN-SAGITTAL SLICES IN PRACTICALLY HEALTHY GIRLS DEPENDING ON THE CHARACTERISTICS OF THE STRUCTURE AND SIZE OF THE BODY - Гунас, І.В.; Пінчук, С.В.; Іваниця, А.О. (World of Medicine and Biology, 2015)
Aim of our work – in healthy girls of Podillia total group and various somatotypes develop regression models of the lumbar spine computed tomography sizes for median-sagittal sections depending on the structural features and body size.Materials and methodsBased on the Scientific and Research Center of Vinnytsia National Medical University named after Pirogov 86 girls (16-20 years) who belong to the Slavonic ethnic group and the third generation living in the Podilsky region of Ukraine, conducted a CT scan of the lumbar spine and chest within the planned prophylactic examinations under voluntary written consent of the studied or their parents.Computer-tomography studies of the lumbar spine were performed using X-ray computer tomography spiral ELscint Selekt SP according to the standard protocol in the study of the spine median-sagittal projection. Morphometry with the involvement precision computer technology and mathematical software of tomograph included definition listed below computed tomographic sizes: anterior, middle, posterior vertebral body height; the average width of the vertebral body, intervertebral disc height; front and rear height of the lumbar spine.Anthropometric investigation was conducted by the method of Bunak. Component composition of body weight was studied by the method of J. Mateigka. To evaluate the somatotype we used a mathematical scheme for the Heath-Carter. Established next somatotypes distribution among the studied women: endomorph – 18; mesomorph - 10; ectomorph - 11; ectomesomorph - 1; endomesomorph - 26; middle-intermediate somatotype - 12. That is why, for further analysis in modeling, we have examined only members of the total group and endomesomorph somatotype.Construction of mathematical models carried out in licensed package «STATISTICA 5,5» by the method of direct incremental regression analysis.Results. DiscussionsFound that out of 15 possible models of computed tomographic sizes height of vertebrae body in girls with endomesomorph somatotype 10 depend on the total complex of anthropometric and somatotypological characteristics more than 60% (R2 from 0.732 to 0.817); all models of intervertebral disc height, medium width vertebral bodies, as well as front and rear height of the lumbar spine also depend on the total complex of anthropo-somatotypological signs of more than 60% (respectively R2 from 0.631 to 0.839, from 0.766 to 0.837, 0.604 and 0.678).In the analysis of computer- tomographic designed models size of the lumbar spine on median-sagittal sections in healthy girls with endomesomorph somatotype found that the most commonly they include cephalometric indicators and covering body size (by 17.8%), thickness of skin and fat folds (17.1%), transversal body sizes (13,2%), the width of distal epiphysis of long bones of limbs (10.9%) and longitudinal dimensions of the body (10.8%). Moreover, to the models vertebrae body height most often includes - cephalometric indicators (by 18.3%), longitudinal body size, width of distal epiphysis of long bones of the limbs and the thickness of skin and fat folds (by 15.0%), transverse and covering body sizes (by 13.3%); to the models of intervertebral disc height - covering body size (25.8%), cephalometric indicators and transverse dimensions of the body (by 19.4%), thickness of skin and fat folds (16.1%); to the models of medium width vertebral bodies - thickness of skin- fat folds (21.4%), covering body size (by 17.6%), cephalometric rates (14.3%), the longitudinal, transverse body size and width of distal epiphysis of long tubular leg bones (by 10.7%).In the total group of healthy girls of Podillia all models of computer-tomographic sizes of lumbar spine median-sagittal sections depend on the total complex of anthropometric characteristics and somatotypological less than 60% (R2
Keywords: computed tomography; lumbar spine; modeling; anthropometry; healthy girls